IBRAMSYAH AMANDIT’S SUFISM POEMS: STUDY OF SUFI AESTHETICS - Hajriansyah, Hajriansyah (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
Tulisan ini membahas tasawuf dalam konteks seni, terutama melalui puisi Sastrawan Ibramsyah Amandit. Keindahan (al-jamâl), sebagai aspek ilahi adalah perhatian para sufi. Dengan kepekaan mereka terhadap al-Jamâl yang mewakili sifat-sifat Tuhan, Para Sufi mengungkapkan pengalaman terdalam mereka, kemudian menjadikannya sebagai bentuk karya seni yang mengilhami orang lain untuk mendekati Sang Pencipta (Allah). Penelitian ini merupakan penelitian deskriptif kualitatif yang mengulas beberapa puisi Ibramsyah Amandit dalam "Badai Gurun Darah". Pendekatan teoritis yang diterapkan dalam penelitian ini adalah hermeneutika estetika sufi. Puisi Ibramsyah mewakili pengalaman spritualitas dengan simbol mistik yang diambil dari tradisi sufisme atau dari pemikiran lokal dan pribadinya dengan kesadaran akan ketuhanan.This paper discuss Sufism in the context of art, especially through the poems of the Poet Ibramsyah Amandit. Beauty (al-jamâl) as an aspect of the divine of God is the attention of Sufis. With the sensitivity of Jamâl, which represent attribute of God, they then express their inner experiences, thus becoming forms of artwork that inspires others to get closer to the Creator (Allah). This literary research is descriptive qualitative that review some poems of Ibramsyah Amandit in Badai Gurun dalam Darah. The theoretical approach that used is the study of Sufi Aesthetics that is hermeneutics. Ibramsyah?s poems represent sprituality experience with mystical symbols that taken from the sufism tradition or from local and personal thought with awareness of divinity.